The Determination of Some Phytochemical Compounds and Antiradical Activities of Urtica dioica L., Morus nigra L., and Glycyrrhiza glabra L. Powder as Feed Additives - Zengin, Muhittin; Sur, Aslıhan; Gokçe, Zehra; Ökkeş; Yılmaz, Okkes; Yilmaz (My University, 2025)
This study was assessed the approximate their antioxidant capacity and certain bioactive components of Glycyrrhiza glabra L., Morus nigra L. and Urtica dioica L.  which can be employed as feed supplements. DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2'-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging tests were carried out to measure the antiradical properties of these plants. The average DPPH radical cleaning activities of Morus nigra L., Glycyrrhiza glabra L.  and Urtica dioica L.’s powder extracts of methanol, were measured as 86.37%, 92.90%, 71.98% respectively. The average ABTS radical cleaning activities of Morus nigra L., Glycyrrhiza glabra L.  and Urtica dioica L.’s powder extracts of methanol were measured as 90.83%, 98.07%, 83.62% respectively. Morus nigra L. was found to contain the highest levels of flavonoid (19.80 ?g GAE/g) and phenolic (40.79 ?g GAE/g) components. It has been measured those phenolic acids and flavonoid were found in different proportions in these plants. While the highest concentration of gallic and hydrocinnamic acid were found in Morus nigra L., vanillic, caffeic and ferulic acids were found in Glycyrrhiza glabra L. and only rosmarinic acid was found in Urtica dioica L. The highest levels of flavonoids were found in Glycyrrhiza glabra L. except for kaempferol. According to the analysis results, it can be said that Glycyrrhiza glabra L. has more effective antiradical and phycochemical effects as feed additive.
Keywords: Urtica dioica L; Morus nigra L; Glycyrrhiza glabra L; Antiradical Activity; Fenolic Acid